2008
DOI: 10.1007/s00247-008-1050-3
|View full text |Cite
|
Sign up to set email alerts
|

Voiding urosonography: the study of the urethra is no longer a limitation of the technique

Abstract: VUS can replace voiding cystourethrography as the method of choice for the initial study of suspected VUR in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 10 publications
1
39
0
1
Order By: Relevance
“…The safety of intravesical CE US in children has been shown with no major associated adverse effects (10), and a comparative study has shown CE US to have a diagnostic accuracy of 90% in comparison to voiding cystourethrography (11). Another application of intraluminal CE US, known as voiding urosonography, also shows potential for evaluating the urethra (12).…”
Section: Discussionmentioning
confidence: 99%
“…The safety of intravesical CE US in children has been shown with no major associated adverse effects (10), and a comparative study has shown CE US to have a diagnostic accuracy of 90% in comparison to voiding cystourethrography (11). Another application of intraluminal CE US, known as voiding urosonography, also shows potential for evaluating the urethra (12).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate that ce-VUS is a practical unique paediatric application of US-CAs that has gained widespread acceptance over the past few years after its introduction in the mid-1990s. Initial restrictions, such as assessment of the urethra, have been overcome, and the potential to combine ce-VUS with sonographic genitography has also been demonstrated [70][71][72][73][74][75]. A recent metaanalysis of the existing literature on comparative studies of ce-VUS with voiding cystourethrography (VCUG) and direct radionuclide cystography (DRNC) confirmed the high sensitivity and specificity of this elegant nonionising imaging modality [76].…”
Section: Discussionmentioning
confidence: 99%
“…These include intravesical CEUS, which has become an option for the diagnosis of vesicoureteral reflux in pediatric patients, 25 and voiding urosonography, which shows potential for evaluating the urethra. 26 Defining novel applications for ultrasound contrast could improve diagnostic and therapeutic options for patients without incurring the exposure of ionizing radiation.…”
Section: Figmentioning
confidence: 99%